Development, trade, and the WTO : a handbook - Hoekman, Bernard M.; Mattoo, Aaditya; English, Philip (Washington, D.C. : World Bank, 2002)
Developing countries are increasingly confronted with the need to address trade policy related issues in international agreements, most prominently the World Trade Organization (WTO). New WTO negotiations on a broad range of subjects were launched in November 2001. Determining whether and how international trade agreements can support economic development is a major challenge. Stakeholders in developing countries must be informed on the issues and understand how their interests can be pursued through international cooperation.This handbook offers guidance on the design of trade policy reform, surveys key disciplines and the functioning of the World Trade Organization (WTO), and discusses numerous issues and options that confront developing countries in using international cooperation to improve domestic policy and obtain access to export markets. Many of the issues discussed are also relevant in the context of regional integration agreements.
Includes index.
Includes bibliographical references (p. 605-628).
rpm 27/09/16
Loans
Keywords: International economic relations; International trade